CHILDHOOD DISADVANTAGE ASSOCIATED WITH GREATER PHYSICAL HEALTH CAPABILITIES IN ADULTHOOD. (11th November 2018) - Allan, A; Munoz, E; Gamaldo, A; Mogle, J; Sliwinski, M; Scott, S
Abstract: Lower socioeconomic status (SES) in childhood is related to poorer physical health in childhood. Relatively few studies examine health outcomes in middle age and late life; even fewer studies examine the long-term impact of public assistance and financial level in childhood on adult health outcomes. We tested retrospective reports of childhood adversity (e.g., major illness, physical abuse, etc.) and childhood disadvantage (e.g. financial level growing up, parent's highest education level, etc.) as predictors of worse objective (e.g., body mass index [BMI]) and subjective (e.g., self-reported physical capabilities) adult health. A total of 339 adults (63% women; 8% Non-Hispanic White, 61% Non-Hispanic Black, 20% Hispanic White, 7% Hispanic Black, 4% Other; Median income: $40, 000 - $59, 000) aged 25 to 65 years (M = 46.72, SD = 11.28) completed surveys as part of a larger study. Analysis of variance results indicated, when covarying for current SES, age, sex, and ethnicity, individuals who received welfare in childhood reported greater physical capabilities (B=-2.92, SE=1.21, p=.02). Older age was associated with lower physical capabilities (B=-0.29, SE=0.05, p<.0001) but did not predict BMI. There was a significant interaction between current age and childhood welfare receipt (B=0.07, SE=0.03, p=.01), such that older individuals who received welfare as children reported worse physical health capabilities compared to their younger counterparts. Logistic regression results indicated, compared to those who rated their financial level in childhood as "worse off than others, " individuals who reported being "about the same as others" were less likely to be overweight or obese (OR=0.27, CI=0.07–0.98, p=.03).